Plasma TVs and Perceived Customer Benefits - Ahmad, Faraz (Indian Journal of Marketing, 2010)
A plasma display panel (PDP) is a type of flat panel display common to large TV displays (32 inches or larger). Many tiny cells between two panels of glass hold an inert mixture of noble gases. The gas in the cells is electrically turned into a plasma which then excites phosphors to emit light. Plasma displays should not be confused with LCDs, another lightweight flatscreen display using different technology. A plasma TV is a high definition alternative to the standard cathode ray televisions sold today. A plasma TV provides sharp images and vibrant colors. Quite often, a plasma TV is designed in a 16:9 ratio for wide screen movie formats, as opposed to the box-like 4:3 ratio of standard televisions.